Certain Type Turbofan Engine Whole Vibration Model with Support Looseness Fault and Casing Response Characteristics. (17th December 2014) - Wang, H. F.; Chen, G.
Abstract : Support looseness fault is a type of common fault in aeroengine. Serious looseness fault would emerge under larger unbalanced force, which would cause excessive vibration and even lead to rubbing fault, so it is important to analyze and recognize looseness fault effectively. In this paper, based on certain type turbofan engine structural features, a rotor-support-casing whole model for certain type turbofan aeroengine is established. The rotor and casing systems are modeled by means of the finite element beam method; the support systems are modeled by lumped-mass model; the support looseness fault model is also introduced. The coupled system response is obtained by numerical integral method. In this paper, based on the casing acceleration signals, the impact characteristics of symmetrical stiffness and asymmetric stiffness models are analyzed, finding that the looseness fault would lead to the longitudinal asymmetrical characteristics of acceleration time domain wave and the multiple frequency characteristics, which is consistent with the real trial running vibration signals. Asymmetric stiffness looseness model is verified to be fit for aeroengine looseness fault model.